2013
DOI: 10.1260/0263-0923.32.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Active Vibration Control of Moving Web with Varying Density

Abstract: Nowadays more and more materials can be manufactured or stored in continuous web form. The vibration of the moving web limits the productivity and quality of the web materials. The active vibration control of the moving web with varying density is considered in this paper. Finite difference method is used to discretize the dynamic equations of the moving web with varying density and derive the state equation of transverse vibration control system for the moving web with varying density. The simulation of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Buchanan 26 analyzed the stability of a circular membrane with linearly varying density in the radial direction. Ma et al 27 employed a suboptimal control method to control the linear vibration of a moving web with variable density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchanan 26 analyzed the stability of a circular membrane with linearly varying density in the radial direction. Ma et al 27 employed a suboptimal control method to control the linear vibration of a moving web with variable density.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al. 27 employed a sub-optimal control method to control the linear vibration of a moving web with variable density.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the influence of system parameters on the stability region was developed. Parametric vibration and dynamic stability of the printing paper web with multi-roller supports and the active vibration control of the web were also studied by Wu et al 35 and Ma et al 36 Nonlinear dynamical analysis of interaction between a three-dimensional rubberlike membrane and liquid in a rectangular tank was studied in Parasil and Watanabe. 37 The large deflection vibration characteristics and stability of the moving membrane are researched.…”
Section: Introductionmentioning
confidence: 99%
“…35 and Ma et al. 36 Nonlinear dynamical analysis of interaction between a three-dimensional rubberlike membrane and liquid in a rectangular tank was studied in Parasil and Watanabe. 37…”
Section: Introductionmentioning
confidence: 99%
“…Gupta and Khanna [17] and Zhou and Wang [18] studied the vibration characteristics of the viscoelastic plate with parabolic variable thickness. The suboptimal control method was applied to control the variable density of the moving web by Ma and her coworkers [19]. Sheet flutter and the interaction between sheet and air were analyzed by Pramila [20]; the results showed that surrounding air had an impact on the critical velocities and the eigenfrequencies.…”
Section: Introductionmentioning
confidence: 99%